Antibiotic-Producing Beneficial Bacteria in the Gut of the Burying Beetle Nicrophorus vespilloides - Heise, Philipp; Liu, Yang; Degenkolb, Thomas; Vogel, Heiko; Schäberle, Till F.; Vilcinskas, Andreas (Frontiers in Microbiology, 2019)
The increasing prevalence of antibiotic-resistant human pathogens is a growing public concern and there is intense pressure to identify new antibacterial compounds that can be developed into antibiotics with novel mode of action. Evolutionary theory predicts that insects that have evolved to occupy sophisticated ecological niches by feeding and reproducing on carcasses will depend on their gut microbiome to prevent colonization by invading pathogens taken up with the diet. This inspired our hypothesis that the complex interactions between the core microbiome and the more flexible microbial communities dependent on the environment may promote the outsourcing of antibiotic synthesis to beneficial microbes. We tested this hypothesis by cultivating and characterizing bacteria isolated from the gut of the burying beetle Nicrophorus vespilloides, which feeds and reproduces on small vertebrate carcasses buried in the soil to avoid competitors such as fly maggots. The chemical extracts of isolated bacteria were screened for activity against human pathogens such as Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Candida albicans. More than 400 strains were isolated, among which the crude extract of Serratia marcescens 2MH3-2 displayed promising activity against Staphylococcus aureus. Bioactivity-guided fractionation enabled purification of the primary antimicrobial compound of the extract. By LC-MS and NMR experiments, it was identified as serrawettin W2 (C38H61N5O9), the antibacterial and nematostatic activity of which was corroborated in our study. We postulate that this antibiotic could contribute to the control of both bacteria and phoretic nematodes in the gut, which compete for food when transferred to the carcass. Our study shows that the gut microbiome of N. vespilloides is a promising resource for the screening of antibiotic-producing bacteria.